2008
DOI: 10.1590/s1516-14392008000400003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of compression strength of granite-epoxy composites using design of experiments

Abstract: This paper presents a processing study of the polymer matrix composite (PMC) developed with an epoxy polymeric matrix reinforced with particulate ceramic granite. This PMC composite has been reported to be used as structural parts of machine tools and Coordinate Measuring Machines due to its superior vibration damping characteristics and reduced processing cycle over cast iron. The investigated processing variables were epoxy content and particle size and the mechanical characterization was carried out by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…In Brazil, there is no company that produces this material, even though there exist in the market Machine Tools built up based upon synthetic granite. Other applications, besides Machine Tools, are the fabrication of optical equipments such as optical microscopes, loupes, image capturing systems, telescopes and laser instruments for medical and dental applications 4 . The size, homogeneity, the ceramic particles purity and the polymers viscosity are some of the processing variables that affect the properties of these composites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, there is no company that produces this material, even though there exist in the market Machine Tools built up based upon synthetic granite. Other applications, besides Machine Tools, are the fabrication of optical equipments such as optical microscopes, loupes, image capturing systems, telescopes and laser instruments for medical and dental applications 4 . The size, homogeneity, the ceramic particles purity and the polymers viscosity are some of the processing variables that affect the properties of these composites.…”
Section: Introductionmentioning
confidence: 99%
“…The polymeric resin viscosity during the mixing step with the granite greatly affects the composite`s structural homogeneity, being difficult the mixing of ceramic particles with a polymeric viscous resin. Defects caused by agglomerated particles of ceramic granite (clusters) can result in reduced composite`s resistance limit 4 . The damping capacity of a material is related to the dissipation of vibration energy in its internal structure, which is constantly supplied by the relative motion and friction of the parts during the operation of a Machine Tool.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that effective thermal conductivity decreases with increase in epoxy content in the mixture. Neglecting the effect of size of crushed granite particles on effective thermal conductivity 16 , the trend observed could be due to the presence of epoxy resin having very low thermal conductivity (0.363 W/m. K), between the granite particles.…”
Section: Resultsmentioning
confidence: 99%
“…The range for study is selected from the literature which indicates that, the preferable range of volume fraction of epoxy content in a mixture is 12%-20%, considering the strength and mechanical properties of the structure developed 15,16 . The mixtures selected for analysis in this study are given in Table 1.…”
Section: Preparation Of Test Samplesmentioning
confidence: 99%